Application of paper mill sludge and additional chemical substances in the production of container cardboard - Halysh, Vita; Trus, Inna; Radovenchyk, Iaroslav; Shabliy, Tetyana; Ivanchenko, Anna; Nikolaichuk, Alina; Gomelya, Nikolai (Eastern-European Journal of Enterprise Technologies, 2022)
The possibility to dispose of paper mill sludge as part of a composition of container cardboard from secondary raw materials has been investigated. The fractional composition of the sludge was studied and it was shown that the main part of the fibers is represented by small particles with a size of up to 1.2 mm. Studying the processes of formation of container cardboard when using paper mill sludge showed that an increase in the consumption of fibrous-inorganic waste leads to a deterioration in the physical and mechanical properties of cardboard. However, the increase in sludge consumption does not affect the surface absorption of water during one-sided wetting. The value of these indicators is within the normal range and is 25 and 70 g/m2, respectively. In addition, an increase in sludge consumption from 10 to 50 % in the manufacture of cardboard leads to a decrease in the degree of fiber retention on the grid from 86.3 to 82.1 %. Regularities of using strengthening additives, namely industrial cationic and anionic flocculants, as well as native corn and modified starches for the strength of cardboard and the quality of sub-grid waters, have been established. Research results show that the effect of flocculants is quite ambiguous. On the one hand, there is a clearly observed positive impact on the quality of the sub-grid waters. This is due to the reduction of their turbidity due to smaller fiber washes. Nevertheless, the positive effect on physical and mechanical parameters is minimal, and in some cases, there is a decrease in strength indicators. The greater the efficiency of keeping fine fiber on the grid when using flocculants, the lower the values of physical and mechanical indicators. In general, when using sludge in the composition of cardboard in combination with flocculants and starch, the indicators were achieved that are considered standard for waste paper container cardboard of grade KT-1 according to TU U 17.1-41085075-002:2017